1976
DOI: 10.1099/00222615-9-3-325
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacteria in the intestinal tract of infants: an in-vivo study

Abstract: PLATE XXIV IT is well known that the nature of the milk fed to newborn infants greatly influences the physico-chemical and microbiological properties of their faeces. The most prominent features of the faeces of breast-fed infants in comparison with those of bottle-fed infants are a preponderance of bifidobacteria, a low pH and a virtual absence of putrefactive organisms, and it has been customary to regard this triad as sequentially related. The results of studies in vivo indicate that although pH does influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1
2

Year Published

1976
1976
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(69 citation statements)
references
References 12 publications
5
61
1
2
Order By: Relevance
“…By the end of the first days the predominant faecal flora was anaerobic. The contribution of the Bifidobacterium spp., Bacteroides spp., Clostridium spp., enterococci and Gramnegative aerobic organisms to the development of faecal flora in this report is essentially similar to the findings of various other studies reported by Mata, Mejicanos & Jimenez (1972), Bullen, Tearle & Willis (1976), Hentges (1980) and , on sequential development of faecal flora of healthy full-term neonates.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…By the end of the first days the predominant faecal flora was anaerobic. The contribution of the Bifidobacterium spp., Bacteroides spp., Clostridium spp., enterococci and Gramnegative aerobic organisms to the development of faecal flora in this report is essentially similar to the findings of various other studies reported by Mata, Mejicanos & Jimenez (1972), Bullen, Tearle & Willis (1976), Hentges (1980) and , on sequential development of faecal flora of healthy full-term neonates.…”
Section: Discussionsupporting
confidence: 92%
“…These studies have shown that the bacterial colonization of the various ecological niches of the body, including those of the gastrointestinal tract (GIT) and the umbilicus, occurs soon after birth. The predominant flora in the first 48 h are facultative organisms but thereafter the neonates usually become colonized by the strict anaerobes to the same, or greater, extent as the facultative species (Mata, Mejicanos & Jimenez, 1972;Bullen, Tearle & Willis, 1976;Long & Swenson, 1977;. The normal resident bacterial flora during the first 10 days of life varies according to the baby's feeds but it usually becomes stable by the end of the first month (Albert et al 1978;Beerens, Romond & Neut, 1980;Shahani & Ayebo, 1980;.…”
Section: Introductionmentioning
confidence: 99%
“…The contributions of bifidobacteria, bacteroides, enterococci and enterobacteria were similar to those found in various studies by Mata et al (1972), Ellis-Pegler, Crabtree and Lambert (1 979, Bullen, Tearle and Willis (1 976), Long and Swenson (1977) and Albert et al (1978). Bifidobacteria are the predominant faecal bacteria in breast-fed infants (Mata and Urrutia, 197 1 ;Bullen et al, 1976) and during the first week of life in infants fed with Premium Milk (Bullen, Tearle and Stewart, 1977). In our studies, bifidobacteria represented c. 25% of all strains identified.…”
Section: Discussionsupporting
confidence: 68%
“…The gut microbiota of preterm infants is less diverse than those of full-term babies (70,73,(82)(83)(84) . There are numerous studies in which the predominance of bifidobacteria in exclusively breast-fed infants has been found (65,66,74,(85)(86)(87)(88) . At age 3-6 weeks, exclusively breast-fed infants harbour higher numbers of bifidobacteria, whereas formula-fed babies have more diverse microbiota, lower numbers of bifidobacteria and higher numbers of Bacteroides, Lachnospiraceae, Lactobacillus group, Clostridium difficile and Coriobacteriaceae (65,71,74,87,89,90) .…”
Section: Agementioning
confidence: 99%